How does the Internet affect trading? Evidence from investor behavior in 401(k) plans - Choi, J (Journal of Financial Economics, 2002)
We analyze the impact of a Web-based trading channel on trader behavior and performance in two large corporate 401(k) plans. After 18 months of Web access, trading frequency at sample firms doubles relative to a control group of firms without a Web channel. Web trades tend to be smaller than trades made through other channels and Web traders tend to have smaller portfolios than other traders, so the Web's impact on portfolio turnover is substantially smaller than its effect on trading frequency. There is no evidence than any of this new trading on the Web is successful.